Mathematic Teachers And Online Learning In The Covid-19 Pandemic: A Survey Study - Farij Imron; Imra’atus Shalihah; Zaharuddin M; Weti Susanti; M. Imamuddin; Isnaniah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The COVID-19 pandemic has had an impact on changes in the implementation of learning. Face-to-face learning before the COVID-19 pandemic turned into online learning during the COVID-19 pandemic. The purpose of this study was to describe the teacher's responses and reasons regarding the implementation of online learning during the covid-19 pandemic. The study was carried out at SMKN Pakong involving five mathematics teachers as informants. Data was collected by interview and continued by analysis. The results of this study include: (1) Teachers more often use WhatsApp application in online learning, because the students are familiar with the use of this application, (2) Teachers prefer to carry out face-to-face learning rather than online learning. It is related to students’ character building and students can be directly monitored by the teachers. (3) The arrangements that must be prepared before online learning are the teachers arrange the necessary equipment such as preparing communication tools, internet quota, ensuring the availability of signals and electricity, preparing materials, power points, learning videos and the examples of the video, (4) Students more understand the subject matter in face-to-face learning, because teachers can immediately correct conceptual errors made by students, (5) Most of the teachers are enjoy in using the lecture method and face-to-face learning, but there are also teachers who prefer to use case study learning and learning using the Problem Based Learning (PBL) model.